Improving Science Knowledge Competence through Guided Inquiry Learning Model Assisted with Audio Visual Media - Anak Agung Istri Putri Ari; Ida Bagus Gede Surya Abadi (Universitas Pendidikan Ganesha, 2020)
The low competence of students' science knowledge due to the lack of optimal use of models when learning makes students difficult to understand learning. The purpose of this study is to analyze the effect of the Guided Inquiry learning model Assisted by the Audio-Visual on the competence of science. This research is a quasi-experimental study with a non-equivalent control group design. The population of this study was 455 students and the study sample was determined using cluster random sampling techniques. Data collection using the test method with instruments in the form of ordinary multiple-choice tests so that the data obtained in the form of science competency values in the form of quantitative data were analyzed using t-test, namely polled variance. The results of the calculation of the data obtained t count = 7,433 > t table = 2,000 at a significance level of 5% (dk = 32+ 32 - 2 = 62) then H0 is rejected and Ha is accepted, which means there is an influence of the Guided Inquiry learning model Assisted by the Audio-Visual with groups being taught through conventional learning in grade 4th elementary school..